Agrobacterium tumefaciens‐mediated nuclear transformation of a biotechnologically important microalga—euglena gracilis - Becker, Ina; Prasad, Binod; Ntefidou, Maria; Daiker, Viktor; Richter, Peter; Lebert, Michael (International Journal of Molecular Sciences, 2021)
Euglena gracilis (E. gracilis) is an attractive organism due to its evolutionary history and substantial potential to produce biochemicals of commercial importance. This study describes the establishment of an optimized protocol for the genetic transformation of E. gracilis mediated by Ag-robacterium (A. tumefaciens). E. gracilis was found to be highly sensitive to hygromycin and zeocin, thus offering a set of resistance marker genes for the selection of transformants. A. tumefaciens‐me-diated transformation (ATMT) yielded hygromycin‐resistant cells. However, hygromycin‐resistant cells hosting the gus gene (encoding β‐glucuronidase (GUS)) were found to be GUS‐negative, indi-cating that the gus gene had explicitly been silenced. To circumvent transgene silencing, GUS was expressed from the nuclear genome as transcriptional fusions with the hygromycin resistance gene (hptII) (encoding hygromycin phosphotransferase II) with the foot and mouth disease virus (FMDV)‐derived 2A self‐cleaving sequence placed between the coding sequences. ATMT of Euglena with the hptII‐2A–gus gene yielded hygromycin‐resistant, GUS‐positive cells. The transformation was verified by PCR amplification of the T‐DNA region genes, determination of GUS activity, and indirect immunofluorescence assays. Cocultivation factors optimization revealed that a higher number of transformants was obtained when A. tumefaciens LBA4404 (A600 = 1.0) and E. gracilis (A750 = 2.0) cultures were cocultured for 48 h at 19 °C in an organic medium (pH 6.5) containing 50 μM acetosyringone. Transformation efficiency of 8.26 ± 4.9% was achieved under the optimized cocul-tivation parameters. The molecular toolkits and method presented here can be used to bioengineer E. gracilis for producing high‐value products and fundamental studies.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Agrobacterium tumefaciens; Euglena gracilis; Gene silencing; Genetic engineering; Transformation

Amino acids as possible alternative nitrogen source for growth of Euglena gracilis Z in life support systems - Richter, Peter; Liu, Y.; An, Y.; Li, X.; Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Krüger, Julia; Schuster, Martin; Ntefidou, Maria; Daiker, Viktor; Haag, Ferdinand; et al. (Life Sciences in Space Research, 2015)
In recent times Euglena gracilis Z was employed as primary producer in closed environmental life-support system (CELSS), e.g. in space research. The photosynthetic unicellular flagellate is not capable of utilizing nitrate, nitrite, and urea as nitrogen source. Therefore, ammonium is supplied as an N-source in the lab (provided as diammonium-dihydrogenphosphate, (NH)HPO) to E. gracilis cultures. While nitrate exerts low toxicity to organisms, ammonium is harmful for many aquatic organisms especially, at high pH-values, which causes the ionic NH4+ (low toxicity) to be partially transformed into the highly toxic ammonia, NH. In earlier reports, Euglena gracilis was described to grow with various amino acids as sole N-source. Our aim was to investigate alternatives for (NH)HPO as N-source with lower toxicity for organisms co-cultivated with Euglena in a CELSS. The growth kinetics of Euglena gracilis cultures was determined in the presence of different amino acids (glycine, glutamine, glutamic acid, leucine, and threonine). In addition, uptake of those amino acids by the cells was measured. Cell growth in the presence of glycine and glutamine was quite comparable to the growth in (NH)HPO containing cultures while a delay in growth was observed in the presence of leucine and threonine. Unlike, aforementioned amino acids glutamate consumption was very poor. Cell density and glutamate concentration were almost unaltered throughout the experiment and the culture reached the stationary phase within 8 days. The data are compared with earlier studies in which utilization of amino acids in Euglena gracilis was investigated. All tested amino acids (glutamate with limitations) were found to have the potential of being an alternative N-source for Euglena gracilis. Hence, these amino acids can be used as a non-toxic surrogate for (NH)HPO.
Keywords: Amino-acids; CELSS; Euglena gracilis; Nitrogen source

Analysis of the Localization of Fluorescent PpROP1 and PpROP-GEF4 Fusion Proteins in Moss Protonemata Based on Genomic “Knock-In” and Estradiol-Titratable Expression - le Bail, Aude; Schulmeister, Sylwia; Perroud, Pierre-François; Ntefidou, Maria; Rensing, Stefan A.; Kost, Benedikt (Frontiers in Plant Science, 2019)
Tip growth of pollen tubes, root hairs, and apical cells of moss protonemata is controlled by ROP (Rho of plants) GTPases, which were shown to accumulate at the apical plasma membrane of these cells. However, most ROP localization patterns reported in the literature are based on fluorescent protein tagging and need to be interpreted with caution, as ROP fusion proteins were generally overexpressed at undefined levels, in many cases without assessing effects on tip growth. ROP-GEFs, important regulators of ROP activity, were also described to accumulate at the apical plasma membrane during tip growth. However, to date only the localization of fluorescent ROP-GEF fusion proteins strongly overexpressed using highly active promoters have been investigated. Here, the intracellular distributions of fluorescent PpROP1 and PpROP-GEF4 fusion proteins expressed at essentially endogenous levels in apical cells of Physcomitrella patens “knock-in” protonemata were analyzed. Whereas PpROP-GEF4 was found to associate with a small apical plasma membrane domain, PpROP1 expression was below the detection limit. Estradiol-titratable expression of a fluorescent PpROP1 fusion protein at the lowest detectable level, at which plant development was only marginally affected, was therefore employed to show that PpROP1 also accumulates at the apical plasma membrane, although within a substantially larger domain. Interestingly, RNA-Seq data indicated that the majority of all genes active in protonemata are expressed at lower levels than PpROP1, suggesting that estradiol-titratable expression may represent an important alternative to “knock-in” based analysis of the intracellular distribution of fluorescent fusion proteins in protonemal cells.<br
Keywords: XFP tagging; genomic knock-in; estradiol-inducible expression; Physcomitrella patens; ROP signaling

Cyanobacterial responses to UV radiation - Lebert, Michael; Ntefidou, Maria; et al. (18TH ESA SYMPOSIUM ON EUROPEAN ROCKET AND BALLOON PROGRAMMES AND RELATED RESEARCH, 2004)
The DNA-weighted irradiance of UV radiation on Mars is about three orders of magnitude higher than on the surface of the Earth. The response of cyanobacteria to UV radiation impinging on the Earths' surface is well known. Several methods are established for these organisms (Hader, 1997; Sinha et al., 2001; Sinha and Hader, 2002). Cyanobacteria may be ideal model systems to study biological effects of physical extremes on the Martian surface, to determine the degree of resistance to extreme stress factors, such as cycles of heat and cold, desiccation and high UV radiation fluxes.

ECOTOX - Biomonitoring based on real time movement analysis of unicellular organisms - Streb, Christine; Richter, Peter; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (18TH ESA SYMPOSIUM ON EUROPEAN ROCKET AND BALLOON PROGRAMMES AND RELATED RESEARCH, 2002)
To meet the todays needs for the protection of the environment from pollution through cumulative poisonings or biohazards ecotoxicology uses biotests, to determine effects of chemicals and sewage waters to ecosystems. ECOTOX is a biotest system that allows both the estimation of risks arising from certain substances or substance mixtures as well as the on-line monitoring of waste waters and aquatic ecosystems. Euglena gracilis, the employed organism for freshwater measurements, found to be highly sensitive to external factors, provides several physiological endpoints, well fitted for toxicity hazard assessment in water management, which can be characterized by the ECOTOX program.

Effects of increased salinity on gravitaxis in Euglena gracilis - Richter, Peter; Börnig, Anke; Streb, Christine; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Journal of Plant Physiology, 2003)
The unicellular freshwater flagellate Euglena gracilis regulates its position in the water column by means of phototactic and gravitactic behavior. Recent experiments have revealed that the cells switch between negative and positive gravitaxis depending upon environmental stimuli such as solar radiation. In this study, the effect of increased salinity on gravitaxis in Euglena gracilis was investigated. In some experiments it was found that salt concentrations up to 5 g L-1 (in some experiments 10 g L-1) increased the motility, velocity and precision of negative gravitactic orientation. Higher salt concentrations decreased all these parameters. At concentrations of about 15 g L-1, cells which did not become immobile, switched from negative to positive gravitaxis. Positive gravitaxis persisted for several hours or even days when the cells were transferred back to standard culture medium. Most of the cells in cultures exposed to salt concentrations above 20g L-1 lost their motility (partial formation of palmella stages) but recovered when transferred back to standard medium or de-ionised water. Post recovery, the cells showed pronounced positive gravitaxis. Additional investigations on the pigmentation, revealed that the cells showed a complete loss of a carotenoid shoulder in the spectrum, which reappeared when the cells were brought back to standard medium.
Keywords: salinity; Euglena gracilis; flagellates; gravitaxis; pigmentation

Gravitational sensory transduction chain in flagellates - Häder, Donat-Peter; Richter, Peter; Ntefidou, Maria; Lebert, Michael (Advances in Space Research, 2005)
Earlier hypotheses have assumed that gravitactic orientation in flagellates, such as the photosynthetic unicell Euglena gracilis, is brought about by passive alignment of the cells in the water Column by being tail heavy. A recent experiment on a sounding rocket (TEXUS 40) comparing immobilized cells with mobile cells demonstrated that the passive buoy effect can account for approximately 20% of the orientation of the cells in a gravity field. The cells show either positive or negative gravitaxis depending oil other external or internal factors. Shortly after inoculation, the tendency of young cells to swim downward in the water Column can be readily reverted by adding micromolar concentrations of some heavy metal ions including copper, cadmium or lead. The negative gravitaxis of older cells is converted into a positive one by stress factors Such as increasing salinity or exposure to excessive visible or UV radiation. The mechanism for this switch seems to involve reactive oxygen species since the gravitactic sign change was Suppressed when oxygen was removed by flushing the cell suspension with nitrogen. Also, the addition of radical scavengers (Trolox, ascorbic acid or potassium cyanide) abolished or reduced the gravitactic sign change. Addition of hydrogen peroxide induced a gravitactic sign change in the absence of external stress factors. The primary reception for the gravity vector seems to involve mechanosensitive ion channels which specifically gate calcium ions inward. We have identified several gene sequences for putative mechanosensory channels in Euglena and have applied RNAi to identify which of these channels are involved in graviperception. The influx of Ca2+ activates calmodulin (CaM) which has been shown to be involved in the sensory transduction chain of graviorientation. It is known that an adenylyl cyclase is bound to the flagellar membrane in Euglena which is activated by CaM. This enzyme produces cAMP which has also been shown to be the key messenger in phototaxis in the same organism by mediating flagellar reorientation and thus swimming path Course correction. (c) 2005 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Euglena; gravitaxis; flagellate; graviperception; mechanosensitive ion channels

High light exposure leads to a sign change in gravitaxis of the flagellate Euglena gracilis - Ntefidou, Maria; Richter, Peter; Streb, Christine; Lebert, Michael; Häder, Donat-Peter (18TH ESA SYMPOSIUM ON EUROPEAN ROCKET AND BALLOON PROGRAMMES AND RELATED RESEARCH, 2002)
In the absence of other external stimuli the motile, unicellular freshwater flagellate Euglena gracilis normally swims upward in the water column (negative gravitaxis). This behavior is most likely triggered by active physiological orientation mechanisms. Recently it was found that negative gravitaxis often inverts to a positive one upon high light exposure. This response is not mediated by the photoreceptor (the paraxonemal body - PAB), because PAB-free mutants do also show this response after high radiation. It is very likely that the phenomenon is triggered by reactive oxygen species, because in the absence of oxygen no gravitaxis sign change was observed. Also increased salinity inverses the sign of gravitaxis, leading to the assumption that environmental stressors induce the formation of reactive oxygen species, serving as signal molecules.

High light exposure leads to a sign change of gravitaxis in the flagellate Euglena gracilis - Richter, Peter; Ntefidou, Maria; Streb, Christine; Faddoul, Jaoudat; Lebert, Michael; Häder, Donat-Peter (Acta Protozoologica, 2002)
The unicellular flagellate Euglena gracilis orients itself in the water column by means of pronounced phototaxis and gravitaxis. The antagonism of phototaxis and gravitaxis brings the cells in a position in the water column providing them with optimal light conditions for their photosynthetic apparatus (about 30 Wm(-2)). Long exposure to solar or artificial radiation induces a loss of the negative gravitactic orientation in Euglena gracilis or very often a pronounced, persistent (>4h) sign change in gravitaxis. The effects on gravitaxis are exclusively due to UV and intensive blue light as experiments with different light qualities revealed. This phenomenon is not caused by the phototaxis photoreceptor or chloroplast processes, because also the colorless and blind (no photoreceptor) Euglena gracilis If mutant and Astasia longa reverse the sign of gravitaxis upon strong radiation. The sign change is oxygen-dependent, because gravitaxis is not affected in oxygen free medium (in wild type Euglena gracilis, as well as in the If mutant and Astasia longa). This indicates the involvement of oxygen radicals as a trigger of gravitaxis sign reversal. As the destruction of the photoreceptor molecules by light leads to a loss of phototaxis, the switch from. negative to positive gravitaxis might be an adaptation mechanism of the cells to escape from deleterious radiation even after loss of the ability to perceive the light direction.
Keywords: Astasia longa; Euglena gracilis; gravitaxis; oxygen; phototaxis; sign change; solar radiation; UV

High light-induced sign change of gravitaxis in the flagellate Euglena gracilis is mediated by reactive oxygen species - Richter, Peter; Streb, Christine; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Acta Protozoologica, 2003)
Euglena gracilis responds to abiotic stress factors (high light, salinity, heavy metals) with a sign change of its gravitactic behavior. This phenomenon is oxygen dependent and can be suppressed by the application of the reductant dithionite. It is not mediated by the photoreceptor since also blind mutants change their movement behavior upon high light exposure. It is also not mediated by the chloroplasts since the gravitactic sign change was also found in white, chloroplast-free mutants. The NO radical donor SNAP and the NO cleaver carboxy-PTIO had no obvious effects on gravitaxis or gravitactic sign change, respectively, indicating that NO radicals are not likely involved in gravitactic sign change. Gravitactic sign change was suppressed when oxygen was removed by flushing the cell suspension with nitrogen. Also, the addition of the radical scavengers Trolox, ascorbic acid or potassium cyanide abolished or reduced gravitactic sign change. Quantification of reactive oxygen species (ROS) in the cells indicated that these treatments reduced the evolution of ROS. Furthermore, addition of hydrogen peroxide induced gravitactic sign change in the absence of external stress factors. These results indicate that gravitactic sign change is triggered by ROS (most likely hydrogen peroxide) which are probably produced by cytochrome-c-oxidase in the mitochondria. The clear responses of Euglena to abiotic stress factors suggest that these cells are probably interesting model systems in the study of stress signaling.
Keywords: Euglena gracilis; gravitaxis; hydrogen peroxide; reactive oxygen species; sign change; UV

Influence of Different Light-Dark Cycles on Motility and Photosynthesis of Euglena gracilis in Closed Bioreactors - Richter, Peter; Strauch, Sebastian; Ntefidou, Maria; Schuster, Martin; Daiker, Viktor; Nasir, Adeel; Haag, Ferdinand; Lebert, Michael (Astrobiology, 2014)
The unicellular photosynthetic freshwater flagellate Euglena gracilis is a promising candidate as an oxygen producer in biological life-support systems. In this study, the capacity of Euglena gracilis to cope with different light regimes was determined. Cultures of Euglena gracilis in closed bioreactors were exposed to different dark-light cycles (40 W/m(2) light intensity on the surface of the 20 L reactor; cool white fluorescent lamps in combination with a 100 W filament bulb): 1 h-1 h, 2 h-2 h, 4 h-4 h, 6 h-6 h, and 8 h-16 h, respectively. Motility and oxygen development in the reactors were measured constantly. It was found that, during exposure to light-dark cycles of 1 h-1 h, 2 h-2 h, 4 h-4 h, and 6 h-6 h, precision of gravitaxis as well as the number of motile cells increased during the dark phase, while velocity increased in the light phase. Oxygen concentration did not yet reach a plateau phase. During dark-light cycles of 8 h-16 h, fast changes of movement behavior in the cells were detected. The cells showed an initial decrease of graviorientation after onset of light and an increase after the start of the dark period. In the course of the light phase, graviorientation increased, while motility and velocity decreased after some hours of illumination. In all light profiles, Euglena gracilis was able to produce sufficient oxygen in the light phase to maintain the oxygen concentration above zero in the subsequent dark phase. Key Words: Euglena gracilis-Bioreactor-Light-dark cycle-Motility-Gravitaxis. Astrobiology 14, 848-858.

Occurrence and conversion of progestogens and androgens are conserved in land plants - Shiko, Glendis; Paulmann, Max Jonas; Feistel, Felix; Ntefidou, Maria; Hermann-Ene, Vanessa; Vetter, Walter; Kost, Benedikt; Kunert, Grit; Zedler, Julie A.Z.; Reichelt, Michael; Oelmüller, Ralf; Klein, Jan (New Phytologist, 2023)
Progestogens and androgens have been found in many plants, but little is known about their biosynthesis and the evolution of steroidogenesis in these organisms. Here, we show that the occurrence and biosynthesis of progestogens and androgens are conserved across the viridiplantae lineage. An UHPLC-ESI-MS/MS method allowed high-throughput analysis of the occurrence and chemical conversion of progestogens and androgens in 41 species across the green plant lineage. Dehydroepiandrosterone, testosterone, and 5α-dihydrotestosterone are plants' most abundant mammalian-like steroids. Progestogens are converted into 17α-hydroxyprogesterone and 5α-pregnane-3,20-dione. Androgens are converted into testosterone and 5α-dihydrotestosterone. 17,20-Lyases, essential for converting progestogens to androgens, seem to be most effective in monocot species. Our data suggest that the occurrence of progestogens and androgens is highly conserved in plants, and their biosynthesis might favor a route using the Δ4 pathway.
CRIS-Team Scopus Importer:2023-08-18
Keywords: androgens; Arabidopsis thaliana; Chlamydomonas reinhardtii; Hordeum vulgare; Physcomitrium patens; progestogens; Spirodela polyrhiza; steroidogenesis

Photoactivated adenylyl cyclase controls phototaxis in the flagellate Euglena gracilis - Lebert, Michael; Ntefidou, Maria; et al. (Plant Physiology, 2003)
Euglena gracilis, a unicellular freshwater protist exhibits different photomovement responses, such as phototaxis (oriented movement toward or away from the light source) and photophobic (abrupt turn in response to a rapid increase [step-up] or decrease [step-down] in the light fluence rate) responses. Photoactivated adenylyl cyclase (PAC) has been isolated from whole-cell preparations and identified by RNA interference (RNAi) to be the photoreceptor for step-up photophobic responses but not for step-down photophobic responses (M. Iseki, S. Matsunaga, A. Murakami, K. Ohno, K. Shiga, C. Yoshida, M. Sugai, T. Takahashi, T. Hori, M. Watanabe [2002] Nature 415: 1047-1051). The present study shows that knockdown of PAC by RNAi also effectively suppresses both positive and negative phototaxis, indicating for the first time that PAC or a PAC homolog is also the photoreceptor for photoorientation of wild-type E. gracilis. Recovery from RNAi occurred earlier for step-up photophobic responses than for positive and negative phototaxis. In addition, we investigated several phototaxis mutant strains of E. gracilis with different cytological features regarding the stigma and paraxonemal body (PAB; believed to be the location for the phototaxis photoreceptor) as well as Astasia longa, a close relative of E. gracilis. All of the E. gracilis mutant strains had PAC mRNAs, whereas in A. longa, a different but similar mRNA was found and designated AlPAC. Consistently, all of these strains showed no phototaxis but performed step-up photophobic responses, which were suppressed by RNAi of the PAC mRNA. The fact that some of these strains possess a cytologically altered or no PAB demonstrates that at least in these strains, the PAC photoreceptor responsible for the step-up photophobic responses is not located in the PAB.

Photoactivated adenylyl cyclase (PAC) genes in the agellate Euglena gracilis mutant strains - Ntefidou, Maria; Häder, Donat-Peter (ROYAL SOC CHEMISTRY, 2005)
The unicellular, green flagellate wild-type Euglena gracilis ( strain Z) and its colorless phototaxis-mutant strains as well as the non-photosynthetic close relative, Astasia longa, possess several genes of the photoactivated adenylyl cyclase (PAC) family. The corresponding gene products were found to be responsible for step-up ( but not step-down) photophobic responses as well as both positive and negative phototaxis. The proteins consist of two PAC alpha (M-r 105 kDa) and two PAC beta ( 90 kDa) subunits. While the proteins were first believed all to be located in the paraxonemal body (PAB), confocal microscopy revealed that Astasia longa as well as some of the mutant strains do not contain a PAB. Immunofluorescence using PAC antibodies showed that the PAC proteins are also located along the total length of the flagellum at least in some of the strains. In order to determine if the genes responsible for the PAC proteins in the PAB and flagella are identical, sequences of all PAC proteins were analyzed in the Euglena and Astasia strains studied for PAC protein location. Full sequence analysis using PCR and 3' and 5' RACE indicated a substantial divergence between strains with a homology between strains of between 45 and 100%. Sequence alignment and sequence tree construction for the main functional groups (BLUF domain, which binds FAD, and adenylyl cyclase) showed that the paca and the pac beta gene products form clusters each with some of the mutants being closely related while others show a substantial degree of genetic diversity. The conclusion of these results is that there is a family of very dissimilar PAC proteins located in the PAB and the flagellum where they serve different functions in phototaxis and step-up photophobic reactions.

Physcomitrium patens PpRIC, an ancestral CRIB-domain ROP effector, inhibits auxin-induced differentiation of apical initial cells - Ntefidou, Maria; Eklund, D. Magnus; le Bail, Aude; Schulmeister, Sylwia; Scherbel, Franziska; Brandl, Lisa; Dörfler, Wolfgang; Eichstädt, Chantal; Bannmüller, Anna; Ljung, Karin; Kost, Benedikt (Cell Reports, 2023)
RHO guanosine triphosphatases are important eukaryotic regulators of cell differentiation and behavior. Plant ROP (RHO of plant) family members activate specific, incompletely characterized downstream signaling. The structurally simple land plant Physcomitrium patens is missing homologs of key animal and flowering plant RHO effectors but contains a single CRIB (CDC42/RAC interactive binding)-domain-containing RIC (ROP-interacting CRIB-containing) protein (PpRIC). Protonemal P. patens filaments elongate based on regular division and PpROP-dependent tip growth of apical initial cells, which upon stimulation by the hormone auxin differentiate caulonemal characteristics. PpRIC interacts with active PpROP1, co-localizes with this protein at the plasma membrane at the tip of apical initial cells, and accumulates in the nucleus. Remarkably, PpRIC is not required for tip growth but is targeted to the nucleus to block caulonema differentiation downstream of auxin-controlled gene expression. These observations establish functions of PpRIC in mediating crosstalk between ROP and auxin signaling, which contributes to the maintenance of apical initial cell identity.
CRIS-Team Scopus Importer:2023-02-24
Keywords: auxin; cell differentiation; CP: Developmental biology; CP: Plants; CRIB domain; initial cells; land plant evolution; nuclear targeting; Physcomitrium patens; RHO/ROP effectors; RHO/ROP GTPases; tip growth

Secretion and Endocytosis in Pollen Tubes: Models of Tip Growth in the Spot Light - Grebnev, Gleb; Ntefidou, Maria; Kost, Benedikt (Frontiers in Plant Science, 2017)
Pollen tube tip growth is a widely used model ideally suited to study cellular processes underlying polarized cell expansion. Local secretion supplying material for plasma membrane (PM) and cell wall extension is essential for this process. Cell wall biogenesis requires fusion of secretory vesicles with the PM at an about 10× higher rate than PM extension. Excess material is therefore incorporated into the PM, which needs to be reinternalized through endocytosis. The classical model of tip growth proposes that exocytosis occurs at the apex and that newly incorporated PM material is transported to adjacent lateral regions, where excess material is endocytically recycled. This model was recently challenged based on studies indicating that lateral exocytosis may be balanced by apical endocytosis. This review provides an overview of published data pertaining to exocytosis, endocytosis and vesicular trafficking in pollen tubes. Its key aim is to present classical and alternative models of tip growth in the light of available experimental data. By necessity, the review focusses on pollen tubes of angiosperm models (Nicotiana tabacum, Arabidopsis, Lilium longiflorum), which have been studied far more extensively and grow much faster than structurally strikingly different gymnosperm pollen tubes. Only major transport pathways are considered, which substantially contribute to the mass-flow of membrane material at the pollen tube tip. Growth oscillation, which may be displayed in particular by fast-growing pollen tubes, are not discussed as their influence on the spatial organization of apical membrane traffic is not understood.
Keywords: pollen tube; tip growth; polarized growth; secretion/exocytosis; endocytosis; membrane recycling

Sensory transduction of gravitaxis in Euglena gracilis - Streb, Christine; Richter, Peter; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Journal of Plant Physiology, 2002)
Euglena gracilis is a single-celled freshwater flagellate which shows, among other movement behaviors, a negative gravitaxis (cells swim upward in the water column) and a pronounced phototaxis. Gravitaxis is most likely an active physiological mechanism, and the influence of various inhibitors on the gravitaxis in Euglena gracilis was tested using the fully automatic image analysis system ECO-TOX to elucidate the possible cellular mechanism of gravity perception and signal transduction. Substances such as the phosphodiesterase inhibitors theophylline, IBM-X and forskolin, which increase the intracellular cAMP concentration, enhance the precision of graviorientation of the cells measured shortly after incubation. Indomethacin, which decreases the intracellular cAMP concentration by inhibition of the adenylate cyclase, inhibited graviorientation. All inhibitors of calmodulin metabolism tested reduced the precision of gravitaxis in Euglena gracilis. Heparin and LiCl, which inhibit the IP3-pathway (block IP3 channels or formation of IP3, respectively) had no effect. The potassium channel blockers BaCl2 and CsCl showed an effect on the orientation behavior, while tetraethylammonium (TEA) had no influence. The protein phosphatase inhibitor, ocadaic acid, inhibited graviorientation at low concentrations. The data are discussed with respect to the current working model for gravitaxis in Euglena gracilis.
Keywords: calmodulin; cyclic nucleotides; Euglena gracilis; flagellates; gravitaxis; sensory transduction

The Extended Synaptotagmins of Physcomitrium patens - Kaier, Alexander; Ntefidou, Maria (Plants, 2025)
Membrane contact sites (MCSs) between the endoplasmic reticulum and the plasma membrane enable the transport of lipids without membrane fusion. Extended Synaptotagmins (ESYTs) act at MCSs, functioning as tethers between two membrane compartments. In plants, ESYTs have been mainly investigated in A. thaliana and shown to maintain the integrity of the plasma membrane, especially during stress responses like cold acclimatization, mechanical trauma, and salt stress. ESYTs are present at the MCSs of plasmodesmata, where they regulate defense responses by modulating cell-to-cell transfer of pathogens. Here, the analysis of ESYTs was expanded to the bryophyte Physcomitrium patens, an extant representative of the earliest land plant lineages. P. patens was found to contain a large number of ESYTs, distributed over all previously established classes and an additional class not present in A. thaliana. Motif discovery identified regions in the Synaptotagmin-like mitochondrial (SMP) domain that may explain phylogenetic relationships as well as protein function. The adaptation mechanisms of P. patens necessary to conquer land and its simple tissue structure make it highly suitable as a model organism to study ESYT functions in tip growth, stress responses, and plasmodesmata-mediated transport, and open new directions of research regarding the function of MCSs in cellular processes and plant evolution.
CRIS-Team Scopus Importer:2025-04-18
Keywords: bryophytes; extended synaptotagmins; lipid transport proteins; membrane contact sites; Physcomitrium patens; plasmodesmata; tip growth

The influence of microgravity on Euglena gracilis as studied on Shenzhou 8 - Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Sperling, Anna; Schuster, Martin; Richter, Peter; Weißkopf, Matthias; Ntefidou, Maria; Daiker, Viktor; An, Y. A.; Li, X. Y.; Liu, Y. D.; et al. (Plant Biology, 2014)
The German Aerospace Center (DLR) enabled German participation in the joint space campaign on the unmanned Shenzhou 8 spacecraft in November 2011. In this report, the effect of microgravity on Euglena gracilis cells is described. Custom-made dual compartment cell fixation units (containing cells in one chamber and fixative - RNA lysis buffer - in another one) were enclosed in a small container and placed in the Simbox incubator, which is an experiment support system. Cells were fixed by injecting them with fixative at different time intervals. In addition to stationary experiment slots, Simbox provides a 1g reference centrifuge. Cell fixation units were mounted in microgravity and 1g reference positions of Simbox. Two Simbox incubators were used, one for space flight and the other as ground reference. Cells were fixed soon after launch and shortly before return of the spaceship. Due to technical problems, only early in-flight samples (about 40min after launch microgravity and corresponding 1g reference) were fully mixed with fixative, therefore only data from those samples are presented. Transcription of several genes involved in signal transduction, oxidative stress defence, cell cycle regulation and heat shock responses was investigated with quantitative PCR. The data indicate that Euglena cells suffer stress upon short-term exposure to microgravity; various stress-induced genes were up-regulated. Of 32 tested genes, 18 were up-regulated, one down-regulated and the rest remained unaltered. These findings are in a good agreement with results from other research groups using other organisms.
Keywords: Euglena gracilis; gene expression; microgravity; qPCR; space flight; unicellular flagellate